Coagulation-Flocculation Process of Nutrient-Rich Suspended Solids from Aquaculture Effluent Using Bioflocculant - Jaganathan, Jaga Sahsiny; Abdullah, Siti Rozaimah Sheikh; Ismail, Nur ‘Izzati; Sharuddin, Siti Shilatul Najwa (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Due to the growth and development of the aquaculture industry, appropriate wastewater treatment is needed to reduce uncontrolled pollution and environmental impacts. Therefore, this research uses green technology method, which is the coagulation-flocculation process to treat aquaculture wastewater. Natural flocculants have been the focus of research of many research due to the negative impact from using chemical flocculant. In this study, the potentiality of local plants of moringa leaves and seed (Moringa oleifera), banana pith (Musa), neem leave (Azadirachta indica) and Pandan leave (Pandanus amaryllifolius) as bioflocculant were studied. This study also focuses on nutrient recovery. The potential of sludge obtained through the coagulation-flocculation process as fertilizer was investigated in comparison with commercial fertilizer. Through this study, it is shown that Moringa oleifera seed recorded the highest rate of suspended solid removal from synthetic kaolin water at 36.7% and highest turbidity removal rate at 34.8%. Previous studies have shown that aquaculture sludge contains 1.27 % of nitrate, 0.32 % of phosphorus and 0.65 % of potassium. The characteristics of sludge produced through the process of coagulation-flocculation resembles organic fertilizer. This shows that treated aquaculture sludge has potential to be used as an organic fertilizer. With this, it can promote the use of sustainable green technology for effective aquaculture wastewater treatment.